Turkey’s development assistance in Africa in the 2000s Hybrid humanitarianism in the post-liberal era - OĞUZ GÖK, GONCA (Macmillan/Palgrave Press, London, 2021)
Africa has always been at the center of various actors’ humanitarian efforts, including states, International Organizations (IOs) and Non-Governmental Organizations (NGOs) throughout its history. Foreign aid was earlier considered to be a strict flow of money and resources from the industrialized democratic Western states conceptualized as North to developing or underdeveloped states of the South in Africa. Since the 2000s, humanitarian efforts have been transforming as Western norms of market liberalism and democracy are in sharp decline. The weakening of liberal democracy is closely associated with major global shifts in the world order since the global financial crisis of 2008. The rising economic power of states from the Global South, such as China, India and Brazil, coincided with a period in which Western states’ economic prosperity, financial resources and normative appeal have been in relative decline (Onis 2017). The popular ideas of post-Cold War neoliberal peace and multilateralism seem to be rapidly deteriorating while authoritarianism and populism is on the rise in almost all parts of the world.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC)